STUDY OF HEPATIC DYSFUNCTION IN DENGUE PATIENT - BAJAJ, SARTHAK; MANDA, GURPREET SINGH; SINGH, HARJAP (International Journal of Current Pharmaceutical Research, 2025)
Objective: To evaluate the prevalence, severity, and clinical outcomes of hepatic dysfunction in dengue patients admitted to the Department of General Medicine at MGM Medical College and LSK Hospital, Kishanganj, Bihar. Methods: A cross-sectional analysis was conducted on dengue-confirmed patients. Liver function parameters, including serum AST, ALT, bilirubin, and alkaline phosphatase levels, were assessed. Demographic and clinical data were analyzed to identify correlations between hepatic dysfunction and disease severity. Results: Elevated AST and ALT levels were observed in 83.3% and 80% of patients, respectively, with severe elevations in 16.7% (AST) and 13.3% (ALT). Mild hyperbilirubinemia occurred in 26.7% and ALP elevation in 33.3% of cases. Jaundice was uncommon (6.7%), predominantly affecting younger adults (18–30 years), with males more frequently involved. Liver enzyme elevations correlated positively with disease severity, peaking in dengue shock syndrome (DSS) cases. Conclusion: Hepatic dysfunction is a frequent and clinically significant complication of dengue fever. Liver enzyme elevations may serve as valuable markers of disease severity. Early recognition and monitoring of hepatic involvement are essential for improving patient outcomes. Further multicenter studies are needed to validate these findings and elucidate underlying mechanisms.